2016
DOI: 10.1186/s13148-016-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association data implicates DNA methylation-mediated genetic risk in psoriasis

Abstract: BackgroundPsoriasis is a chronic inflammatory skin disease characterized by epidermal hyperproliferation and altered keratinocyte differentiation and inflammation and is caused by the interplay of genetic and environmental factors. Previous studies have revealed that DNA methylation (DNAm) and genetic makers are closely associated with psoriasis, and strong evidences have shown that DNAm can be controlled by genetic factors, which attracted us to evaluate the relationship among DNAm, genetic makers, and diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…As expected, the differentially methylated genes identified in the skin are mostly associated with epidermal and keratinocyte differentiation, and cellular regeneration [39, 7476]. Four skin biopsy-based studies identified members of the S100A family, part of the epidermal differentiation complex, as top differentially methylated hits [39, 40, 7578]. Many studies have failed to identify differences in skin biopsies in affected non-inflamed skin compared to healthy controls [39, 75, 76].…”
Section: Dna Methylation Studies In As Ibd and Psoriasismentioning
confidence: 77%
See 2 more Smart Citations
“…As expected, the differentially methylated genes identified in the skin are mostly associated with epidermal and keratinocyte differentiation, and cellular regeneration [39, 7476]. Four skin biopsy-based studies identified members of the S100A family, part of the epidermal differentiation complex, as top differentially methylated hits [39, 40, 7578]. Many studies have failed to identify differences in skin biopsies in affected non-inflamed skin compared to healthy controls [39, 75, 76].…”
Section: Dna Methylation Studies In As Ibd and Psoriasismentioning
confidence: 77%
“…IL13 , ALOX5AP , PTHLH and TNFSF11 ) [38, 70, 75, 76]). This was observed in Zhou et al (2017) where 3 unique CpG sites were identified with 11 associated SNP-CpG pairs within C1orf106 , DMBX1 and SIK3 [39, 40, 64]. C1orf106 regulates adherence junction stability, although the key gene at this locus remains unclear [79].…”
Section: Dna Methylation Studies In As Ibd and Psoriasismentioning
confidence: 89%
See 1 more Smart Citation
“…Concerning the contribution of DNA methylation to Ps or PsA, deregulation of the global methylation pattern has been found in psoriatic lesions 83‐85 . In particular, the promoting region of Epidermal Differentiation Complex ( EDC locus, 1q21.3) genes has been found hypomethylated.…”
Section: Epigeneticsmentioning
confidence: 99%
“…It seems that new methods to suppress the JAK-STAT pathway could involve the use of epigenetic mechanisms of the expression of genes connected with the said pathway. The epigenetic strategies were described as a new possibility to treat, for instance, cancers [ 14 , 15 ], mental diseases [ 16 ] and psoriasis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%